Degradation Behaviour of a High CSR Coke in an ExperimentalBlast Furnace: Effect of Carbon Structure and Alkali Reactions - Hilding, Tobias; Gupta, Sushil; Sahajwalla, Veena; Björkman, Bo; Wikström, Jan-Olov (ISIJ International, 2005)
A high CSR coke was tested in the LKAB's Experimental Blast Furnace (EBF) at Luleå. The evolution of physical and chemical properties of the centre-line coke samples were analysed by Light Optical Microscopy (LOM), BET N2 absorption and SEM/XRF/XRD. Alkali distribution in the EBF cokes was examined by XRF/SEM and EDS. Thermo Gravimetric Analysis (TGA) was used to measure isothermal and non-isothermal CO2 reactivity of the cokes. The crystalline order of carbon and the concentration of alkalis were found to increase as the coke descended through thermal reserve zone to the cohesive zone of the EBF. The crystallite height (Lc) of EBF coke carbon displayed a linear correlation with the measured EBF temperatures demonstrating the strong effect of temperature on carbon structure of coke in the EBF. Alkali concentration of the coke was increased as it descended into the EBF, and was uniformly distributed throughout the coke matrix. The CO2 reactivity of lower zone cokes was found to increase when compared to the reactivity of the upper zones cokes, and was related to the catalytic effect of increased alkalis concentration. The deterioration of coke quality particularly coke strength and abrasion propensity were related to coke graphitisation, alkalization and reactivity. Coke graphitisation is shown to have a strong influence on the coke degradation behaviour in the EBF. Validerad; 2005; 20061210 (ysko)